DIET-ASSOCIATED INFLAMMATION, PHYSICAL ACTIVITY, AND HEALTH-RELATED OUTCOMES IN ULCERATIVE COLITIS. (22nd January 2022) - DuBois, Kelli; Blake, Christine; Rudisill, Caroline; Harrison, Sayward; Hébert, James
Abstract: INTRODUCTION: Individuals diagnosed with Ulcerative Colitis (UC) often seek complementary lifestyle methods, such as diet and physical activity, to self-manage disease symptoms and respond to the psychosocial challenges of living with chronic illness. The Energy Adjusted Dietary Inflammatory Index (E-DII TM ) measures the inflammatory potential of one's food intake and has never been studied among the UC population. This study aimed to test the associations between E-DII scores, physical activity, and UC related health outcomes. METHODS: Data obtained from participants in the IBD Partners e-cohort who self-reported UC (n=2, 052) were analyzed using a cross-sectional, secondary data analysis. Patients who had undergone UC-related surgery were excluded. Dietary data collected through a National Cancer Institute food frequency questionnaire were converted into an E-DII score. Physical activity data were collected using the Godin-Shephard Leisure Time Activity Index. Outcome variables included the Simple Clinical Colitis Activity Index (SCCAI), Short Inflammatory Bowel Disease Questionnaire (SIBDQ), and PROMIS domains of anxiety, depression, fatigue, sleep disturbance, and satisfaction with social role. Multivariable regression models controlled for age, sex, BMI, race, education, diet, physical activity, smoking status, medication class, and disease duration. RESULTS: A higher E-DII score (indicating pro-inflammatory dietary intake potential) was significantly associated with increased disease activity (β=0.166; p<0.001), reduced health-related quality of life (β= -0.056; p<0.001), increased anxiety (β=0.342; p=0.006), increased depression (β=0.408; p=0.004), increased fatigue (β=0.386; p=0.005), increased sleep disturbance (β=0.339; p=0.003), and decreased satisfaction with social role (β= -0.370; p=0.004). Leisure Time Activity was inversely associated with disease activity (β= -0.108; p<0.001), anxiety (β= -0.025; p=0.001), depression (β= -0.025; p=0.001), fatigue (β= -0.058; p<0.001), and sleep disturbance (β= -0.019; p=0.008), while positively associated with IBD-related quality of life (β=0.005; p<0.001) and satisfaction with social role (β=0.063; p<0.001). The benefit among health outcomes, excluding depression, was greater for strenuous exercise intensity than for moderate or mild intensities. For all outcomes, interaction effects between E-DII and physical activity were not significant. DISCUSSION: These findings suggest that an anti-inflammatory diet and physical activity are each complementary lifestyle methods that may contribute to decreases in disease activity, anxiety, depression, and fatigue, as well as improvements in health-related quality of life, sleep, and satisfaction with social role. Such modalities may aid in managing systemic and localized inflammation associated with UC and reduce the burden of UC on daily living.